KEANEKARAGAMAN IKAN DI PERAIRAN TELUK KENDARI SULAWESI TENGGARA [Fish Diversity in Kendari Bay, Southeast Sulawesi] - Asriyana Asriyana; M. F. Rahardjo; S. Sukimin; D. F. Lumban Batu; E. S. Kartamihardja (Masyarakat Iktiologi Indonesia (Indonesian Ichthyological Society), 2009)
Research on fish diversity was carried out from August to October 2009 with three times of sampling in three stations in Kendari Bay, Southeast Sulawesi. Fish collection using experimental gillnets (with different mesh sizes %, 1, 1%, 1%, 2, 3, and 4 inch) and seser (0 1 meter and mesh size 0.04 inch). During research, 45 species of 30 families were collected. Based on individual quantities, at the first sampling, Sardinella fimbriata was dominant species on Station I and II, S. longiceps on Station III; in the second sampling, S. fimbriata was dominant species on Station I, S. longiceps on Station II, Plotosus canius on S3; in the third sampling, Ambassis sp. was dominant species on Station I, S.longiceps on Station II, Upeneus suphureus and Stolephorus commersonii on S3. Diversity index (H’) was range between 0.512.25, dominance index (C) was range between 0.16-0.83 and evenness index (E) was range between 0.19-0.75.